Mewujudkan Perekonomian Perempuan: Studi Kualitatif Efektivitas Program Simpan Pinjam Khusus Perempuan (SPP) Bagi UMKM Jepara - Frenaldo Zain Rahmandani; Bonnix Hedy Maulana; Sukma Wijayanti (Jurnal Akuntansi Bisnis, 2026)
This study aims to analyze the effectiveness of the SPP Program in supporting the development of women's MSMEs in Mayong District. The research uses a qualitative approach with a phenomenological method through in-depth interviews, observations, and documentation of women entrepreneurs, UPK managers, SPP cadres, and village officials. Data analysis was carried out through the stages of data reduction, data presentation, and interactive conclusion drawing with triangulation of sources and methods to ensure the validity of the findings. The results show that the program's SPP effectiveness is reflected in its socialization mechanisms, loan application and verification processes, easy requirements, village-based fund disbursement, and selection and monitoring systems accompanied by institutional assistance. This program has been proven to increase access to capital, strengthen business capacity, and encourage the empowerment and economic independence of women. Overall, SPP contributes positively to business stability and the strengthening of women's economic role at the village level.